Concerning the correlation between the concepts of «military crime» and «the composition of a military offense» - Сергій Олександрович Харитонов (Проблеми Законності, 2018)
The article contains a complex analysis of the correlation between the notions of «military crime» and «the composition of a military offense». The author supports the position that the notion of «military crime» is specific to the generic concept of «crime», enshrined in art. 11 of the Criminal Code of Ukraine.